Dietary Fructus sophorae extracts supplementation improved production performance, antioxidant capacity, and intestinal microbiota in broiler chickens - Yang, Xiyi; Zheng, Yan; Wei, Peihua; Wei, Jiandong; Yuan, Xuejun; Jiang, Shuzhen; Yang, Weiren; Jiao, Ning (Frontiers in Veterinary Science, 2026)
IntroductionThis study was conducted to examine the effects of Fructus sophorae extracts (SE) on the production performance, serum biochemistry and antioxidant, intestinal morphology, and cecal microbiota of broilers.MethodsA total of 1,088 1-day-old Arbor Acres (AA) broiler chickens were randomly assigned to four treatment groups with 8 replicates each and 34 chickens per replicate. Broilers received basal diets supplemented with 0 (CON), 100 (SE100), 150 (SE150), and 200 (SE200) mg/kg SE for 42 days, respectively.Results and discussionThe results showed that SE had no significant effect on the growth performance of broilers. However, SE supplementation significantly increased the organic matter and crude ash metabolic rates but decreased serum alkaline phosphatase activity (p < 0.05). In addition, 150 and 200 mg/kg SE supplementation increased serum total protein and total cholesterol contents (p < 0.05). SE supplementation also improved the antioxidant capacity by decreasing serum and liver malondialdehyde contents and by increasing serum glutathione peroxidase and liver superoxide dismutase (SOD) activities (p < 0.05). On the other hand, 150 and 200 mg/kg SE supplementation increased serum SOD activity (p < 0.05). Moreover, SE supplementation improved liver morphology. In addition, 150 and 200 mg/kg SE supplementation improved duodenal and ileal morphology by increasing villus height and villus height to crypt depth ratio (p < 0.05). Furthermore, SE supplementation balanced the intestinal microbiota composition and improved the microbial diversity. In conclusion, dietary 150 mg/kg SE supplementation could improve nutrient utilization efficiency, biochemical metabolism, antioxidant capacity, and intestinal and liver health in broilers, considering feed cost. This study provides a basis for SE application in broiler production